Remilitarização do Japão: uma desconstrução da imagem do Japão pacífico - Cubota, Juliana Dalmaso (2024)
There is a lot of evidence that suggests that Japan's security policy has undergone several structural reforms that have resulted in a process of remilitarization. At end of World War II and with the eventual US occupation of the Japanese territory, Japan promulgated its famous “pacifist constitution” in 1947, in which, in its 9th article, its demilitarization was formalized. However, over the years, despite various mechanisms to prevent its remilitarization, Japanese conservative policymakers, have created an agenda for the reinterpretation of the article, as well as gradually trying to break the ties that prevented the country from increasing its military capacity. This is because due to the major changes in the international system caused by the Cold War, as well as domestic pressures, the country found itself in a situation in which the resurgence as a military actor was seen as “inevitable”